Inovasi Pengelolaan Limbah Ternak dengan AL-K dan Zeolit: Solusi Ramah Lingkungan di Kelompok Tani Ternak Sadak Seketeng Sumbawa, Nusa Tenggara Barat - Sudirman Sudirman; Asrul Hamdani; Wening Kusumawardani (Indonesian Publication Center, 2026)
The community service program implemented at the Sadak Seketeng Livestock Farmers Group (KTT) aims to improve the knowledge and skills of KTT Sadak members in managing livestock waste using AL-K spraying and zeolite sprinkling technology. This program was implemented through a training method that involved evaluation with pre-tests and post-tests to measure the increase in participants' knowledge. In addition, measurements of fecal pH and ammonia gas levels in the pen were also conducted to assess the impact of the technology implementation. The evaluation results showed a significant increase in knowledge among training participants, with the percentage of improvement varying between 7.14% and 90%. The application of AL-K technology proved effective in lowering fecal pH, thereby reducing excessive acidity levels, while the zeolite sprinkling successfully absorbed ammonia gas and reduced humidity in the pen, creating a cleaner and more comfortable environment. Another positive impact was the reduction in odors from livestock feces, which has the potential to improve air quality around the pen and farmer comfort. This program successfully achieved its goal, namely to improve the knowledge and skills of KTT Sadak members in environmentally friendly livestock waste management. To support the sustainability of the program, it is recommended that training be conducted periodically with regular mentoring and evaluation, so that partners can continue to develop their abilities in managing livestock waste more effectively and sustainably.